Credible Transitions in Eastern Europe: a Perspective from the Theory of Traverse and Systemic Change - Stefano Zamagni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1993)
The best way to think of the transition from a centrally planned to a market economy is as a traverse from one growth path to another. However, question of traverse are as yet relatively understudied as are issues of disequilibrium dynamics of a market or a planned system. The economics of transition currently in process cuts across issues of traverse and of disequilibrium (as evidenced by excess demand, repressed inflation, excess liquid balances) to a market economy characterised by an eventual equilibrium. The paper suggests how economic theory can tentatively cope with the formidable difficulty of this task. Moreover, the paper defends the thesis that it is a major mistake to start a transition process before knowing where a country wants to go. This mistake is the main source of considerable human costs and unnecessary hardship which Eastern European Countries are currently experiencing.
Keywords: 330